Psikoedukasi dalam Meningkatkan Keterlibatan Akademik Mahasiswa di Sekolah Tinggi Ilmu Hukum (STIH) Painan - Raja Oloan Tumanggor (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
During college, various factors influence students' low academic engagement. Emotional pressure, academic stress, and an unsupportive social environment are often the main causes of students' lack of academic activity. However, academic engagement is a crucial factor that significantly influences academic success. Academic engagement itself is a multidimensional construct encompassing emotional, behavioral, and cognitive aspects of students' learning experiences. In general, academic engagement is influenced by internal factors, such as emotional state, learning interest, self-efficacy, and intrinsic motivation; and external factors, such as social environment, peer support, parental involvement, and the teaching style of lecturers. Students at the Painan College of Law (STIH) are not immune to this challenge, especially those who attend weekend employee classes. They face the dual pressures of work responsibilities, family obligations, and academic obligations. This can certainly reduce their focus and energy in optimally participating in lectures. Therefore, academic engagement is a crucial issue that needs to be addressed systematically to ensure students maintain their enthusiasm for learning. Through the Community Partnership Program (PKM), efforts are being made to provide students with a deeper understanding of the importance of academic engagement. The purpose of this activity is for students to understand the factors that influence academic engagement and develop strategies to address them. The methods used in this PKM include presentations, interactive discussions, and self-development and academic planning exercises. Through this activity, it is hoped that students will develop adequate awareness and skills in time management, self-regulation, and internal motivation to remain engaged in academic activities.